Development and Assessment of Levetiracetam Microspheres Utilizing Synthetic and Natural Polymers: A Biomedical Engineering Perspective - Tatapudi Sowjanya; Alladi Saritha (International Journal of Biomedical Innovations and Engineering, 2024)
In the present study, comparative study of Levetiracetam loaded microspheres using Ethyl cellulose as synthetic and Sodium alginate as natural polymers was done. Solvent evaporation and ionic gelation technique has been successfully employed to produce Levetiracetam loaded ethyl cellulose and sodium alginate microspheres with optimal drug encapsulation that sustained the drug release over a period of time. Based on the pre-formulation studies E1 to E4 and S1 to S4 batches were prepared using selected polymers. Prepared microspheres were evaluated for the percentage yield, drug content, drug entrapment efficiency and in-vitro dissolution test. The data obtained from the in-vitro release showed highly correlated with Korsmeyer-Peppas model and Regression was found to be 0.9957 with 1.2 as a n value. The release kinetic study has shown that drug release from microspheres follows the Korsmeyer Peppas as the drug release occurs super case II transport with erosion. For optimised formulation, the drug entrapment efficiency was 91.5%, Percentage yield was 77.3%, and Drug content was 85.7%. Comparison was made between the best formulations E3 and S3 of microspheres prepared by using Ethyl cellulose as synthetic and Sodium alginate as natural polymers respectively. Among these formulations, microspheres prepared by using ethyl cellulose as polymer was found to be best formulation with highest drug content of 85.7%, entrapment efficiency of 91.5%, Percentage yield of 77.3% and in-vitro drug release 88.55% for 16 h and ethyl cellulose polymers was found to be the best formulation for the preparation of novel drug delivery system for Levetiracetam. While control of drug release profile has been a major aim of pharmaceutical research and development of past decade, control of Gl transmit profile could be the focus of next few decades and might result in the availability of products with better therapeutic possibilities and substantial benefits for patients. Dosing frequency and loss of drug also reduced by the use of such type of formulations and the bioavailability of drugs can also be increased. All the above studies reveal that the microsphere can serve as an ideal drug delivery system for Levetiracetam loaded microspheres. Further studies can be done on the stability on Levetiracetam loaded microspheres and the improvement in therapeutic efficacy due to the targeting effort on to the specific receptor sites.
Keywords: Formulation; Levetiracetam; Microspheres; Scanning electron Microscope; evaluation